Contribution of Islamic Law to the Indonesian Constitutional System (Legislative Challenges Amid Legal and Religious Pluralism) - Manto, Nurhayati (Innovative: Journal Of Social Science Research, 2024)
Islamic law's impact on Indonesia's constitutional system is examined in this research, particularly as it pertains to the incorporation of sharia principles into rules and legislation derived from Pancasila and the Republic of Indonesia's 1945 Constitution. In light of religious and legal plurality, the key question that arises is the function of Islamic law within the framework of national law and the challenges that Islamic legal legislation encounters. Analyzing primary and secondary legal texts pertaining to Islamic law and Indonesia's constitution is the research technique used, which is a normative approach. The research also draws attention to pertinent ideas that explain the evolution and integration of Islamic law into the national legal system, including the theory of reception in complexu, the theory of receptie, and the theory of acceptance of legal authority. This study's findings highlight the ways in which Islamic law has shaped Indonesian law, particularly in the areas of family and civil law and the establishment of religious courts. Nevertheless, challenges include, among other things, the fact that Islamic law must be applied in a diverse Indonesian society while also respecting the idea of pluralism. Other obstacles that impact the development of Islamic law regulation include political and societal concerns.